Treatment of Large and Complicated Scalp Defects with Free Flap Transfer. (10th January 2020) - Chen, Fanfan; Ju, Hongbin; Huang, Anfei; Yi, Yongjun; Cao, Yongfu; Xie, Wei; Wang, Xinliang; Fu, Guo
Abstract : Background . Large scalp defects, especially those complicated by calvarial defects, titanium mesh exposure, or cerebrospinal fluid (CSF) leak, pose a challenge for the neurosurgeon and plastic surgeon. Here, we describe our experience of reconstructing the complex scalp defect with free flap transfer. Methods . From October 2012 to September 2017, 8 patients underwent free flap transfer for the reconstruction of the scalp or complicated scalp and calvarial defects. Five patients presented with scalp tumor and the other 3 patients with scalp necrosis or ulceration (2 patients with titanium plate exposure). Seven anterolateral thigh flaps and one radial forearm flap were harvested and employed. The clinical data, including defect characteristics, flap type, complications, and outcomes, were recorded and analyzed. Results . Five patients were pathologically diagnosed with malignant tumor, and 3 of them were given further radiotherapy. For the 2 patients with exposure of titanium plate, no titanium plate was removed. For the patient with scalp necrosis after decompressive craniectomy accompanied by CSF leakage, the CSF leak was stopped after reconstruction. The size of the flaps ranged from 3 to 14 cm in width and 4 to 18 cm in length. No flap failure occurred in these cases. From follow-up to the present, no ulceration or necrosis occurred. Conclusions . Free flap transfer is an ideal method for the reconstruction of large, complicated scalp defects with a one-stage operation. The anterolateral thigh flap is favored because of its durability, adjustability, water tightness, and infection prevention.